Evaluation of hybrid implant in posterior edentulous maxilla with inadequate bone - Aabu Varghese, Dr.; Varghese Mani, Dr.; Sankar Vinod V, Dr.; Arun George, Dr. (Journal of Oral and Dental Sciences, 2021)
Aim of this study is to investigate. Hybrid implant has got satisfactory results in our previous study in various edentulous areas with inadequate bone for endosseous implant placement .The credibility of the implant in the areas of posterior maxilla needed to be evaluated. Objectives â€¢Â Â Â Â Â To evaluate the hybrid implant postoperatively 18 months for gingival status, pain, peri-implantitis and mobility, so that it can be applied in posterior maxillary edentulous spaces with inadequate bone as an alternative to conventional implant. Materials and methods 15 patients were rehabilitated in the posterior edentulous areas with hybrid implant. we intended to study the rehabilitation of posterior maxillary edentulous space i.e. Maxillary- premolar, 1st molar and 2nd molar area with hybrid implant and evaluate the hybrid implant post operatively for 18months (1stmonth, 3rd month, 6th month ,12 th month,18thmonth). Results â€¢Â Â Â Â Â During the study period the implant system presented with no gingivitis, peri-implantitis, and pain. â€¢Â Â Â Â Â The periotest test values show the implant system to be very much stable. â€¢Â Â Â Â Â Also proves to be safe, economical and clinician and patient friendly compared to other implant systems. Conclusion â€¢Â Â Â Â Â Hybrid implant system proves to be very effective in rehabilitating the posterior maxillary regions with inadequate bone. â€¢Â Â Â Â Â Also proves to be safe, economical and clinician and patient friendly compared to other implant systems. Â Â Â